Palaeomagnetic study of Lower Jurassic marine strata from the Neuquén Basin, Argentina: A new Jurassic apparent polar wander path for South America - Iglesia Llanos, María Paula (2006)
A thorough palaeomagnetic study in four marine sedimentary sections from the Neuquén Basin in west-central Argentina was carried out. Sections are several hundreds meters-thick and consist of ammonite-bearing beds with intercalated volcanics. Two magnetic components carried by titanomagnetites were identified in the studied sections, one soft corresponding most likely to a present-day remagnetisation and a harder one which is interpreted as the primary magnetisation of the sections, based on optical studies and the results of field tests of palaeomagnetic stability, bearing an Early Jurassic age. As a result, two new palaeomagnetic poles for stable South America are presented: one for the Hettangian–Sinemurian located at 223° E, 51° S, A95=6°, N=25, and the other for the Pliensbachian–Toarcian located at 67° E, 74° S, A95=5°, N=52. These and other poles from the literature were used in this study to construct a refined Late Triassic to Jurassic APW path for stable South America, which differs significantly from previous models in showing a cusp between the Sinemurian and the Pliensbachian, indicative of large apparent polar wander. The same feature is observed in other continents of Pangea, like Eurasia. Palaeolatitudes of the Neuquén Basin indicate that South America was subject to considerable N–S movements during the Late Triassic and lowermost Early Jurassic. These latitudinal movements of Pangea are consistent with displacements recorded for marine faunas from South America and Eurasia.